VOTERS TO SETTLE SMOKING ISSUE (Tufts Archival Research Center, 2007)
Copy; Marginalia; Article from Mar Vista News on California Proposition 5. Interviews the Campaign for Clean Air (sponsor) leader and discusses the issue of clean indoor air. Identifies opposition to the proposition, including major tobacco corporations, which argues, as Californians for Common Sense, that Prop. 5 violates the Bill of Rights and that enforcement would be impossible.